Factors associated with long-term progression of pediatric chronic kidney disease of nonglomerular etiologies - Chih-Chia Chen; Hsin-Hsu Chou; Yuan-Yow Chiou (Journal of the Formosan Medical Association, 2019)
Background/Purpose: The aims of this study were to determine the long-term associated factors for chronic kidney disease (CKD) progression in a pediatric group with non-glomerular (non-GN) etiologies. Methods: Pediatric patients with a presumptive diagnosis of CKD were enrolled to this study. Recorded information included demographic and laboratory information. We included the patients with non-GN etiologies and investigated the factors including systolic and diastolic blood pressure (BP), proteinuria, and anemia status in association with reductions in the estimated glomerular filtration rate (eGFR). Results: A total of 308 children were enrolled and the mean duration of follow-up was 4.40 ± 3.53 years. Median baseline age was 5 years old and the males represented 55% of all patients. One-unit increased baseline systolic BP z-score was associated with 1.2 ml/min per 1.73 m2 (95% CI = −2 to −0.5) faster rate of eGFR decline. The presence of baseline proteinuria and anemia were also associated with 4.1 ml/min per 1.73 m2 (95% CI = −5.7 to −2.5) and 2.2 ml/min per 1.73 m2 (95% CI = −3.6 to −0.8) more rapid eGFR declination, respectively. Hypertension, anemia and proteinuria during the follow-up were also associated with 3.25 ml/min per 1.73 m2 (95% CI = −5.32 to −1.18), 4.34 ml/min per 1.73 m2 (95% CI = −7.25 to −1.43) and 4.97 ml/min per 1.73 m2 (95% CI = −8.23 to −1.71) more rapid eGFR declination, respectively. Conclusion: Elevated systolic BP, proteinuria, and anemia are independently associated with CKD progression in pediatric patients with non-GN etiologies. Keywords: Chronic kidney disease, Progression, Children, Congenital anomalies of the kidney and the urinary tract